(untitled) (Revista de Investigaciones Universidad del Quindío, 2013)
Pyrolysis of scrap tires is presented as an excellent alternative for the treatment of this waste to produce high-added value compounds. The scrap tires rubber was subjected to pyrolysis under an inert atmosphere at a pressure of 1 bar relative, using a fixed bed reactor. The main objective is to maximize the liquid and solid yields during the pyrolysis. The process parameters such as particle size, reaction time and temperature were analyzed allowing studying their impact on products yield. The models established for the liquid and char yields evidence that the variable with lower influence on the products yield is the particle size. Based on the proposed models it is observed that the best conditions for the maximization of the products depend on the right combination of temperature and reaction time.